Isolasi dan Karakterisasi Morfologi Bakteri Dekomposer Asal Rhizosfer Tanaman Bambu dari Kabupaten Sidrap, Sulawesi Selatan - Mu'minah; Darmawan; Baso Darwisah; Junyah Leli Isnaini; Abdul Mutalib; Muh. Dzulkifly Ashan; Sarief Ismail; Erny Yuniarti (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2025)
The utilization of microorganisms that can accelerate the composting process is the utilization of decomposing bacteria from decomposer products that are useful for accelerating the decomposition process of organic materials. This study aims to obtain bacterial isolates that can function as agricultural waste decomposers from bamboo rhizosphere from Sidrap Regency. This study consists of 4 stages, namely (i) Sampling in the bamboo plant rhizosphere, (ii) Isolation of rhizosphere soil samples, (iii) Identification of microorganism morphology, (iv), and the last stage is testing the ability to degrade cellulose (cellulolytic). The study results showed that in Sidrap Regency, there were 4 sampling points, namely at S 030 57 '25.4